KINERJA GURU DALAM PEMBELAJARAN PERKEMBANGAN KOGNITIF ANAK USIA DINI DI TK/PAUD SE-GUGUS KAYANGAN LOMBOK UTARA - Putri Tria Hartina; Fahruddin; Ni Luh Putu Nina Sriwarthini; I Nyoman Suarta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
A teacher is an instructor who plays a very important role in the world of education. Teachers have a big influence on the creation of quality educational processes and outcomes. In the teaching and learning process, the most important thing for a teacher to pay attention to is the teacher's performance, as a teacher must have good performance so that he can understand students, can create a conducive, creative and innovative learning atmosphere so that children's development reaches an optimal level. This research aims to identify teacher performance in learning early childhood cognitive development in kindergartens throughout the Kayangan Cluster, North Lombok. The type of research used was survey research with a population of 33 group B teachers from 18 kindergartens institutions. The sampling technique used was Sample Random Sampling and the results were obtained from 25 teachers from 12 kindergartens institutions. Research data was obtained using questionnaire and observation techniques. The results of this research show that teacher performance, namely the ability to prepare learning plans, the ability to carry out learning, and the ability to carry out evaluations/assessments of learning outcomes can influence children's cognitive development in a way that is still less than optimal, because many of the indicators that are carried out fall into the sometimes or rarely category. done.